Correlates of misperception of breast cancer risk among Korean-American Women. Issue 6 (17th August 2016) - Kim, Jiyun; Huh, Bo Yun; Han, Hae-Ra
ABSTRACT: In this study, the authors investigate the factors associated with misperception of breast cancer risk, including unrealistic optimism and unrealistic pessimism, among Korean-American women (KAW). Baseline data were collected between March 2010 and October 2011 from 421 KAW aged 40–65 years who participated in a community-based randomized intervention trial designed to promote breast and cervical cancer screening. Multivariate multinomial regression was performed to identify correlates of misperception of breast cancer risk among KAW. A total of 210 KAW (49.9%) had breast cancer risk perception consistent with their objective risk, whereas 50.1% of KAW in the study had some form of misperception of risk. Specifically, 167 participants (39.7%) were unrealistically optimistic about their own breast cancer risk; 44 (10.5%) were unrealistically pessimistic. In multivariate multinomial logistic regression analysis, living with a partner and higher education were significantly associated with higher odds of having unrealistic optimism. High social support is associated with a lower likelihood of having a pessimistic risk perception. Higher worry is associated with a higher likelihood of having unrealistic pessimism. Misperception of breast cancer risk among KAW and related factors must be considered when developing behavioral interventions for this population.